Studi Tentang Penyerapan Nilai Agama Islam dalam Kepemimpinan Tradisional Jambi - Habibudin Ritonga, Habibudin Ritonga; Sururudin, Sururudin (Kontekstualita, 2009)
People in Jambi used to imitate their kingâs Habits, It coudes integration between culture and Islamic doctrine. The process of integration through the whole aspects of life. Leadership for Jambiâs Society id categorized into 3 parts, those are. Pangku Syara. Pangku Adat and Leader in Government. Those must be cooperative Harmony and united in one system.